1985
DOI: 10.1021/bi00346a043
|View full text |Cite
|
Sign up to set email alerts
|

In vitro conversion of a methionine to a glutamine-acceptor tRNA

Abstract: A derivative of Escherichia coli tRNAfMet containing an altered anticodon sequence, CUA, has been enzymatically synthesized in vitro. The variant tRNA was prepared by excision of the normal anticodon, CAU, in a limited digestion of intact tRNAfMet with RNase A, followed by insertion of the CUA sequence into the anticodon loop with T4 RNA ligase and polynucleotide kinase. The altered methionine tRNA showed a large enhancement in the rate of aminoacylation by glutaminyl-tRNA synthetase and a large decrease in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 18 publications
3
57
1
Order By: Relevance
“…Northern blot analysis of total tRNA isolated from COS1 cells transfected with the U35A36 mutant initiator tRNA gene showed that this tRNA was in fact not aminoacylated by any of the endogenous aminoacyl-tRNA synthetases in COS1 cells (data not shown). However, we found that similar to the corresponding U35A36 mutant of E. coli initiator tRNA (54,62), this tRNA could be aminoacylated by E. coli GlnRS. Therefore, all functional studies of the human initiator tRNA mutants carrying the U35A36 anticodon sequence change were performed with cells also expressing E. coli GlnRS.…”
Section: In Vitro Studies With Rabbit Reticulocyte Cell Extracts (I)mentioning
confidence: 61%
“…Northern blot analysis of total tRNA isolated from COS1 cells transfected with the U35A36 mutant initiator tRNA gene showed that this tRNA was in fact not aminoacylated by any of the endogenous aminoacyl-tRNA synthetases in COS1 cells (data not shown). However, we found that similar to the corresponding U35A36 mutant of E. coli initiator tRNA (54,62), this tRNA could be aminoacylated by E. coli GlnRS. Therefore, all functional studies of the human initiator tRNA mutants carrying the U35A36 anticodon sequence change were performed with cells also expressing E. coli GlnRS.…”
Section: In Vitro Studies With Rabbit Reticulocyte Cell Extracts (I)mentioning
confidence: 61%
“…tRNAs are extremely poor substrates for E. coli MetRS (23) and are in fact aminoacylated with glutamine (22,24). (ii) The increase in initiation activity of the mutant depends on the extent of overproduction of MetRS (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The assay measures the ability of a mutant initiator tRNA (T35A36) carrying an anticodon sequence change from CAU to CUA to initiate protein synthesis by using UAG as the initiator codon in a mutated chloramphenicol acetyltransferase (CAT) gene (CATaml.2.5). Mutant tRNA with this anticodon sequence change is now a substrate for E. coli glutaminyl-tRNA synthetase (GlnRS) (22,24). Consequently, initiation from UAG occurs with fGln instead of fMet.…”
mentioning
confidence: 99%
“…N-terminal sequencing to determine the influence of altered IF3 on the site of initiation used in the pSG416 lacZ construct+ b-Galactosidase was purified from the R131P IF3 mutant containing the pSG416 plasmid+ The yield in picomoles for selected PTH amino acids analyzed for the first five cycles is shown+ the CAT reporter gene (Mandal et al+, 1996)+ Based on the results of the toeprinting studies cited above, we considered it likely that the low activity of these altered initiator tRNAs was due, in part at least, to IF3 discrimination, which senses these mutant tRNAs effectively as noninitiator species+ We asked, therefore, if this discrimination was ameliorated in IF3 mutants+ The wildtype strain and both of the IF3 mutants were transformed with a lacZ plasmid, pSG500, in which the initiation codon was altered to UAG+ These strains were then transformed with plasmids carrying the wild type or each of the altered initiator tRNAs (Fig+ 1)+ Assays of b-galactosidase from each of the IF3/initiator tRNA combinations showed that the R99L and R131P IF3 mutants stimulated the activity of each of the mutant initiator tRNAs approximately fivefold (Table 2)+ As a result of the changes to the anticodon loop, the initiator tRNAs used here are charged with glutamine (Schulman & Pelka, 1985;Varshney & RajBhandary, 1990)+ N-terminal sequencing of b-galactosidase isolated from the R99L IF3 mutant carrying plasmid pSG500 confirmed that glutamine was inserted at the UAG initiation codon (Fig+ 3), with no evidence of initiation from internal sites or initiation with methionine+ These data indicate that IF3 mutants that fail to discriminate against non-AUG codons also fail to discriminate against noninitiator tRNAs+ Because of unanticipated problems with plasmid instability, we were unable to measure the activities of the wild-type UAG-decoding tRNA (i+e+, the U35 A36 mutant with no changes in the anticodon stem) or the C30:G40/U35 A36 mutant in the slow-growing infC135 strain carrying multiple plasmids and expressing high levels of b-galactosidase+ However, the activity of the wild-type, U35 A36, UAG-decoding initiator tRNA was unaffected by the R99L IF3 mutant, indicating that, as expected, IF3 does not discriminate against wild-type initiator tRNA decoding of a cognate initiation codon+ These data indicate that the defect in initiator tRNAs carrying alterations in the three anticodon stem G-C pairs was due, at least in part, to discrimination by wild-type IF3+…”
Section: Altered Discrimination Of Initiating Trnas By If3 Mutantsmentioning
confidence: 99%